An Analysis of Juridical Determination of Market Value Fees for Acquisition of Inheritance Type Land and Building Rights by Regional Revenue Agency of Malang City - Sandi Permana Nugraha; Tunggul Anshari Setia Negara; Dyah Widhiawati (East Asian Journal of Multidisciplinary Research, 2023)
The state has the power to collect taxes from its citizens. Article 23 A of the 1945 Constitution of the Republic of Indonesia is the constitutional basis for tax collection by the government, namely the "Central Government" and "Local Government". This study aims to (1) analyze and find out how the mechanism for determining the market value in the collection of BPHTB Inheritance by Bapenda in Malang City, (2) analyze and find out the legal certainty regarding the market value in collecting BPHTB Inheritance by Bapenda in Malang City. This research is normative juridical research. The results show that the collection of Inheritance BPHTB by Bapenda Malang City does not yet reflect the value of legal certainty because the legal rules regarding market value that are used as guidelines by Bapenda also do not have legal certainty.